2017
DOI: 10.11604/pamj.2017.26.167.10861
|View full text |Cite
|
Sign up to set email alerts
|

Gestion de l’Anémie des patients hémodialysés chroniques : cas du Service de Néphrologie et d’hémodialyse du CHU du Point G au Mali

Abstract: IntroductionL'anémie est une complication fréquente de l'IRC couramment retrouvée chez les patients hémodialysés chroniques. Chez ces derniers, la prise en charge est principalement basée sur l'administration d'érythropoïétine et la supplémentation en fer. Le but de ce travail était d'évaluer la prise en charge de l'anémie des hémodialysés chroniques dans le service de Néphrologie du CHU du Point G.MéthodesIl s'agissait d'une étude transversale réalisée dans ledit service du 1er au 31 Août 2016.RésultatsAu tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…In Morocco, it was present in 58.3% of patients [21]. Anemia was the dominant specific cardiovascular risk factor in 95.16% of cases, compared with 87.3% [9] for Fongoro et al [8]. Normocytic normochromic anaemia was present in 48.27% of cases.…”
Section: Clinicalmentioning
confidence: 94%
See 1 more Smart Citation
“…In Morocco, it was present in 58.3% of patients [21]. Anemia was the dominant specific cardiovascular risk factor in 95.16% of cases, compared with 87.3% [9] for Fongoro et al [8]. Normocytic normochromic anaemia was present in 48.27% of cases.…”
Section: Clinicalmentioning
confidence: 94%
“…The majority of patients (71%) had low incomes. Other studies carried out in the same department by Fongoro et al, Togo, and Amekoudi reported 49.30%, 60% and 65% of cases respectively [7] [8] [9]. Low socio-economic status was a barrier to consultation and management in emergency dialysis.…”
Section: Sociodemographicsmentioning
confidence: 99%